Clarifying Misconceptions and Recentring the Debate on Heritable Human Genome Editing in South Africa: A Response to De Vries - Donrich Thaldar (Potchefstroom Electronic Law Journal)
This article responds to recent criticisms by Professor Jantina de Vries regarding my research group's position on the legal status of heritable human genome editing (HHGE) in South Africa. De Vries challenges our interpretation of section 57 of the National Health Act (NHA), questions the methodology of our deliberative public engagement study, and speculates about the broader intentions behind our work. In this response, I clarify our interpretation of section 57 using established principles of statutory interpretation and show that the provision prohibits reproductive cloning but does not ban HHGE outright. I address misconceptions surrounding the scope and structure of the provision, and demonstrate why an interpretation that bans HHGE would result in internal inconsistency. I also defend the methodological soundness and peer-reviewed credibility of our public engagement research, and respond to concerns about our broader strategic intent. Finally, I propose a constructive path forward: a context-sensitive regulatory framework for HHGE grounded in constitutional values, public health priorities and rigorous ethical oversight. The article aims to re-centre the debate on substantive legal and governance issues and invites evidence-based academic engagement on the future of HHGE in South Africa. In doing so it contributes to a more principled and legally coherent foundation for regulating advanced biotechnologies in constitutional democracies.